What Is Economic Self-Sufficiency? Validating a Measurement Scale for Policy, Practice, and Research. Issue 2 (2nd April 2016) - Hetling, Andrea; Hoge, Gretchen L.; Postmus, Judy L.
ABSTRACT: Economic self-sufficiency has emerged as a policy goal of antipoverty programs in many nations. Although the policy direction of these programs is clear, the definition and measurement of economic self-sufficiency is not. This study revisits a scale that was designed in 1993 and has experienced a growth in use after two decades of little attention. Using exploratory and confirmatory factor analysis and bivariate correlations, the scale's validity was tested with a sample of low-income survivors of intimate partner violence. The discussion focuses on how the resulting Scale of Economic Self-Sufficiency–14 (SESS-14) relates to policy, practice, and research.